2006
DOI: 10.1016/j.ydbio.2006.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal regulation of germ cells by activin: The establishment of the initial follicle pool

Abstract: Mammalian females enter puberty with follicular reserves that exceed the number needed for ovulation during a single lifetime. Follicular depletion occurs throughout reproductive life and ends in menopause, or reproductive senescence, when the follicle pool is exhausted. The mechanisms regulating the production of a species-specific initial follicle pool are not well understood. However, the establishment of a follicular reserve is critical to defining the length of reproductive cyclicity. Here we show that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
193
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(210 citation statements)
references
References 58 publications
12
193
1
1
Order By: Relevance
“…Activin was originally isolated based on its ability to stimulate the synthesis and secretion of FSH (de Kretser & Robertson 1989). Recently, it has been shown that activin promotes the establishment of the primordial follicle pool because neonatal activin treatment significantly increases the number of primordial follicles (Bristol-Gould et al 2006). Activin expression and downstream signaling are suppressed in neonatal ovaries exposed to estrogen (Kipp et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Activin was originally isolated based on its ability to stimulate the synthesis and secretion of FSH (de Kretser & Robertson 1989). Recently, it has been shown that activin promotes the establishment of the primordial follicle pool because neonatal activin treatment significantly increases the number of primordial follicles (Bristol-Gould et al 2006). Activin expression and downstream signaling are suppressed in neonatal ovaries exposed to estrogen (Kipp et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the involvement of GDF9 in follicle formation, addition of GDF9 to hamster ovaries in organ culture promotes the formation of follicles (Wang & Roy 2004). Mouse ovaries exposed to another TGFB family member, activin A, have an increased number of primordial follicles (Bristol-Gould et al 2006). Supporting the role of activin in primordial follicle formation, more MOFs are observed in mice that overexpress the activin antagonist, inhibin B (McMullen et al 2001).…”
Section: Growth Factors and Signaling Moleculesmentioning
confidence: 91%
“…Studies in rodents have revealed that steroids and members of the TGF superfamily, including GDF9 and BMP15, are involved in this process (Bristol-Gould et al 2006;Sanchez and Smitz 2012). The development of primary follicles to the late preantral and early antral stages involves follicular growth, fluid-filled antrum formation and oocyte enlargement and an increase in volume and size (Bachvarova et al 1985;Durinzi et al 1995;Eppig and O'Brien 1996;Picton et al 1998).…”
Section: Tgfb Superfamily Gene Expression During Oogenesismentioning
confidence: 99%